pH, ELETRIC CONDUCTIVITY AND LEVELS POTASSIUM THIS SOIL AFTER THREE YEARS APLLIEDS NITROGEN AND POTASSIUM AT THIS PLUM, AT ARAUCARIA COUNTY PARANA – BRAZIL - DOLINSKI, Marcos Antonio; MOTTA, Antonio Carlos Vargas; SERRAT, Beatriz Monte; MAY-DE MIO, Louise Larissa (Scientia Agraria, 2009)
The objective of this research aim was to evaluate after tree years nitrogen and potassium fertilization of plum (Prunus salicina), cv. ‘Reubennel’, this effect in the pH, conductive electric and levels potassium this soil, in the projection ray and middle alley. The experiment was conducted in Araucaria (Brazil) and design was a split-plot in a randomized complete block with three replications. Main plot treatments were potassium rates (55 and 110 kg of K2O ha-1 ano-1), and subplot treatments were the nitrogen rates (40, 80, 120, 160 and 200 kg of N ha-1 ano-1), during the seasons 2003, 2004 and 2005, in the soil type Cambisol not irrigated. The place of collection of the soil under the canopy and in the middle alley, were analyzed was analyzed as split-split plot. Three years of different rates of nitrogen and potassium, was not effect of pH, electrical conductivity and K in the soil. The soil pH ranged from 5.6 to 6.1 until 40 cm depth, was not influenced by N application, due to combined effect of sort-term application, low potential acidification of N source (urea), and residual effect of large application of limestone at orchard establishment. Soil available K was also high and was not influenced by levels K applications during three years. Higher values for soil pH, electric conductivity and K from samples collected canopy compared to middle alley, can explain the results for localized application of limestone and fertilizer on canopy area.